2000
DOI: 10.1097/00002030-200009290-00003
|View full text |Cite
|
Sign up to set email alerts
|

Immune activation in Africa is environmentally-driven and is associated with upregulation of CCR5

Abstract: Immune activation in African residents is environmentally driven and not genetically predetermined. This immune activation results in a skewing of the CCR5 : CXCR4 ratio which is associated with a prevalent isolation of R5 viruses. These data suggest that the selection of the predominant virus strain within the population could be influenced by an immunologically driven pattern of HIV co receptor expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(100 citation statements)
references
References 32 publications
5
94
1
Order By: Relevance
“…1). In accordance with other studies of individuals living in rural Africa (4,8,19), basal immune activation levels were high and were significantly increased by HIV-2 infection. In the selected patients, as well as in the rest of the HIV-2 cohort, immune activation levels for both CD4 and CD8 lymphocytes were correlated with the viral load in Ps and showed a significant difference between NPs and Ps ( Fig.…”
Section: Resultssupporting
confidence: 92%
“…1). In accordance with other studies of individuals living in rural Africa (4,8,19), basal immune activation levels were high and were significantly increased by HIV-2 infection. In the selected patients, as well as in the rest of the HIV-2 cohort, immune activation levels for both CD4 and CD8 lymphocytes were correlated with the viral load in Ps and showed a significant difference between NPs and Ps ( Fig.…”
Section: Resultssupporting
confidence: 92%
“…Third, immune activation (largely measured as increased expression of CD38 þ and HLA-DR þ on T-cells) has also been shown to be inversely correlated with IL-7Ra expression on CD4 T-cells in HIV-infected patients, 45,46 and immune activation has a negative impact on CD4 T-cell recovery. [47][48][49] Although we did not compare the immune activation levels in the UARTO and Caucasian patients, numerous studies have described a higher degree of immune activation both in HIVuninfected [50][51][52][53][54] and HIV-infected African patients [53][54][55][56] as compared with patients from high-income countries owing to differences in the environment 52 and prevalence of other co-infections. 51 The combined effects of poorer CD4 T-cell gain owing to increased T-cell activation and a reduced expression of IL-7Ra on T-cells may potentially negate any beneficial effects of increased IL-7 availability.…”
Section: Discussionmentioning
confidence: 95%
“…This high viral load seen in our population may be due to the constant immune activation that is driven environmentally. [10] Increased HIV replication in activated CD4…”
Section: It Is Reported That the Mean Cd4mentioning
confidence: 99%
“…[10][11] In this context, it was found that the AUC for the viral loads were low when compared to CD4 + T cells indicating lower accuracy of viral load levels in classifying different CDC categories.…”
Section: It Is Reported That the Mean Cd4mentioning
confidence: 99%